Trainability: A matter of gene variants? - Ring-Dimitriou, S.; Kedenko, I.; Humenberger, M.; Feichtinger, R.; Stangl, J.; Andress, M.; Steinbacher, P.; Förster, H.; Müller, E.; Paulweber, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Beside exercise prescription single-nucleotide polymorphism (SNP) in genes important for mitochondria function such as PPARGC1A and PPARD have been reported to affect the change in anaerobic threshold in a retrospective study (Stefan et al., 2007). Therefore we prospectively investigated a 10-wk training response of men with SNP in these genes. Methods: Genotyping (TaqMan, ABI 7900HT) was performed in 838 sedentary males for SNP in PPARGC1A (rs8192678) and PPARD (rs2267668). After intervention (supervised 10 wks cycling, 3x 60 min, HR@70-90% VO2peak) n=28 remained for post tests (59±7 yrs, 27.6±4.1 kg/m² BMI, 36.3±6.9 ml/kg/min VO2peak). Subjects were assigned to wild type (WT=13), SNP1 (minor risk allele for PPARGC1A, WT for PPARD, n=6), and SNP2 (risk alleles for both genes, n=9). Trainability was determined as the relative change in work rate P@VT (point of optimal respiration), P@AT (anaerobic threshold), and P@RCP (respiratory compensation point) based on gas exchange analyses (ZAN680, nSpire Health, US) during incremental cycling (Ergoline, Schiller). Mean differences within and between groups were determined by ANOVA with p<0.05. The study was approved by the Salzburg Ethics Committee and funded by National Bank of Austria (J14156). Results: Significant differences were found within WT in P@VT (99±21 vs. 122±19 W, p=.005) and @RCP (155±25 vs. 185±29 W, p=.009) only. P@RCP was significantly lowest in SNP1 compared to SNP2 and WT (%, 3±9 vs. 12±5 vs. 20±15; F=4.6, p=.02). VO2@VT and @RCP were significantly lower in SNP1 and SNP2 compared to WT (%, 2±10 vs. 4±13 vs. 18±15, F=3.6, p=.04, and 0±8 vs. 6±5 vs. 17±16 vs., F=4.8, p=.02, respectively). Discussion: In line with the findings of Stefan et al. (2007), we found a fiminished exercise effect at sub maximal performance level of untrained males with SNPs. The short-term response at these levels of >15% in WT was sufficient compared to other reports (Skinner et al., 2001) and could probably serve as trainability markers regarding to Vollaard et al. (2009). Although the power of our study is limited due to sample size and sex selection, our data indicate that the trainability of aerobic performance could be affected by gene variants.